Penerapan E-Government pada Website SIKER Dinas Tenaga Kerja Kota Semarang Sebagai Upaya Peningkatan Pelayanan Publik - Fadhil Indra Pradipa; Neny Marlina (Journal of Politic and Government Studies, 2026)
This study aims to analyze the implementation of e-government through the Employment Information System Website (SIKER) at the Department of Manpower of Semarang City and to assess the extent to which the platform ensures inclusive access to public services for all segments of society. This research employs the frameworks of Good Governance, New Public Service, and Policy Implementation Theory to understand digital governance, public service orientation, and the process of implementing technology-based policies. The method used is descriptive qualitative research, with data collection techniques including interviews, documentation, and literature review. The research informants consist of the Head of the Department of Manpower of Semarang City and the SIKER website administrators, with data analysis conducted using an interactive model involving data reduction, data presentation, and conclusion drawing. The results show that the implementation of SIKER has improved efficiency, transparency, and ease of access to employment services, such as AK1 registration (Job Seeker Card), job vacancy information, job training, and industrial relations complaints. Integration with national and provincial systems has further expanded service coverage and supported data-driven decision-making through analytical features. However, several challenges remain, including data synchronization issues across platforms, limited accessibility features for persons with disabilities, and gaps in digital literacy and internet infrastructure in certain areas, which affect the optimal distribution of service access. In conclusion, the implementation of SIKER as a form of e-government has supported the principles of good governance and the smart city transformation in Semarang City, particularly in terms of effectiveness and transparency of public services. However, to achieve truly inclusive and equitable services, it is necessary to strengthen digital infrastructure, enhance human resource capacity, improve system integration, and develop outreach and assistance strategies for vulnerable groups to ensure they are not left behind in the digital transformation process.